The Role of Subjective Norms in the Relationship between Personal Values, Organizational Climate and Knowledge Sharing Behavior - Othman, Siti Zubaidah; Mohd Isa, Mohd Faizal; Balozi, Mohamed Abbasi (2018)
This study examines the direct relationship between personal values, organizational climate and knowledge sharing behavior.The study also investigates the mediating effect of subjective norms on the relationship between personal values, organizational climate and knowledge sharing behavior. A total of 650 questionnaires were personally distributed to respondents from five Tanzanian public hospitals (Muhimbili National Hospital, Ligula Referral Hospital, Mnazi Mmoja Hospital, Sekou Toure Reginal Hospital Mwanza and Mbeya Referral Hospital) after permission was granted by the hospital management. Hypotheses for this study were tested using Partial least squarestructural equation modeling (PLS-SEM). The results show that personal values, organizational climate and subjective norms were positively significantly related to knowledge sharing behavior.Also, both personal values and organizational climate were positively related to subjective norms.Meanwhile, the findings for mediating effect showed that subjective norms mediate the relationship between personal values and knowledge sharing behavior and between organizational climate and knowledge sharing behavior.